Python for Kids: Designing an Educational Literacy Application - Ramdani , Dani; Adiprabowo , Tjahjo; Maulana , Septian; Nurdiansyah, Sansan (Internet of Things and Artificial Intelligence Journal, 2025)
The ability to read and write (Literacy skill) is an essential thing that needs to be known early by children. Children can build applications such as simple games, desktop applications, and websites, several programming languages support the development of children's thinking skills such as C++ on Arduino boards, Raspberry Pi, and other Microcontrollers. Python and MicroPython are also easy to learn, as well as the development of Artificial Intelligence (AI) and its Platform which is so rich in libraries, applications, and other applications. In creating applications with certain extensions, compatibility, and also speed when applied to all PCs in general. This research discusses comprehensively how to build a simple Python-based application by converting voice and text, and this application can be applied to the general public, especially for Kids and also disabilities.